Minat Program Magang Mahasiswa Indonesia Di Sheraton Taoyuan Hotel - Pratama, Bintang Mulya; Resmi, Prasiwi Citra; Widagdo, Yohanes Martono (Lembaga Teewan Journal Solutions, 2026)
Intership programs serve as an important means of developing practical skills aligned with industry neesd. This study aims to measure Indonesian students interest in the overseas internship program at Sheraton Taoyuan Hotel, Taiwan, using a quantitative descriptive approach. Data were collected through a Likert-scale questionnaire from 19 student respondents majoring in hospitality and tourism. The results show an overall average interest score of 78.2%, classified as high. The perceived-benefit indicator obtained the highest score (92.9%), followed by intention to participate (89.1%), while clarity of registration information stood at 77.5%. These findings indicate a positive perception among students toward the added value of cross-country work experience, although concerns remain regarding Mandarin language proficiency, cultural adaptation, and distance from family. The study recommends strengthening foreign language training, cultural adaptation sessions, and greater transparency regarding costs and scholarships so that student interest can be translated into actual participation in international internship programs.